MD simulations of the central pore of ryanodine receptors and sequence comparison with 2B protein from coxsackie virus - Schilling, Roman; Fink, Rainer; Fischer, Wolfgang (Biochimica et biophysica acta. Biomembranes, 2014)
The regulation of intracellular Ca2+ triggers a multitude of vital processes in biological cells. Ca2+ permeable ryanodine receptors (RyRs) are the biggest known ion channels and play a key role in the regulation of intracellular calcium concentrations, particularly in muscle cells. In this study, we construct a computational model of the pore region of the skeletal RyR and perform molecular dynamics (MD) simulations.
Available online 21 December 2013
Gesehen am 25.08.2020